Effect of emotion-based nutrition messages on consumption of calcium-rich foods among early adolescents in Ogbomoso, Nigeria - Oluwaseun Ariyo; Olubunmi Alabi; Elizabeth O. Aleru; Tomilola J. Ojo (Elsevier, 2023)
Introduction: Calcium is a vital micronutrient for several physiological processes, yet it remains one of the significant shortfall nutrients among Nigerian adolescents. Objective: This study was designed to assess the effect of emotion-based nutrition messages on the consumption of calcium-rich foods among early adolescents in Ogbomoso, Nigeria. Methodology: The quasi-experimental study involved 220 adolescents (experimental: 110 and control: 110) selected using a three-stage sampling procedure. A semi-structured, interviewer-administered questionnaire was used to collect socio-demographic characteristics, dietary practice, calcium-rich foods consumption pattern, calcium intake, and anthropometric parameters. Second, calcium-rich foods consumption pattern was assessed using a food frequency questionnaire, and intake was evaluated using the multi-pass 24-hour dietary recall to define adequacy at intake level ≥1,300 mg per day. Third, the experimental group had five weeks of nutrition education using emotion-based nutrition messages. Data were analyzed using descriptive statistics and the Chi-square test at p < 0.05. Results: The age of respondents (years) in experimental (12.88±1.41) and control (13.4±1.03) groups was similar. Primary dietary calcium sources were meat, chicken, egg, white beans, cheese, soy milk, oranges, and locust beans at baseline. At post-intervention, intake of other calcium-rich foods such as milk, yogurt, ice cream, okra, sardine, and unripe plantain increased, however, calcium intake remains similar in both control (238.41±92.4 mg; 235.40±92.92 mg) and experimental groups (239.76±51 mg; 241.46±100.89 mg) at baseline and post-intervention, respectively. The overall calcium intake of the adolescents remains below the recommended intake level of 1,300 mg. Conclusion: Emotion-based nutritional messages did not significantly increase the total calcium intake among early adolescents.